Organizational Justice and Employee Performance in Banking: Mediating Roles of Intrinsic Motivation and Job Satisfaction - Sabara, Saldiansyah; ., Nasrul; Yusuf, Hayat; Masri, Muhammad (Journal of Cultural Analysis and Social Change, 2025)
This study employs a quantitative explanatory approach to examine the causal relationships among organizational justice, extrinsic motivation, intrinsic motivation, job satisfaction, and employee performance. The research was conducted at PT. Southeast Sulawesi Regional Development Bank (BPD Sulawesi). The population consisted of 1,002 permanent employees, and a sample of 285 respondents was determined using the Slovin formula with a 5 percent error level and selected through proportional random sampling. Data were collected using a five-point Likert scale questionnaire. The analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that organizational justice has a positive and significant effect on extrinsic motivation, intrinsic motivation, and job satisfaction. Job satisfaction also has a significant positive effect on employee performance. In addition, extrinsic motivation and intrinsic motivation partially mediate the relationship between organizational justice and job satisfaction. These findings show that employee performance is influenced by both organizational factors and individual psychological factors. Organizational justice encourages employees to feel motivated and satisfied with their work, which in turn enhances performance.